Takhrij and Syarah Hadith of Agrotechnology: Soil Quality for Farming - Yusniar Nur Syahidah; Wahyudin Darmalaksana; Adjat Sudrajat (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a qualitative type through literature study and field studies with the approach of taklirij and sharah hadith. The results and discussion of this study is to determine the quality of soil that is good for farming which is important for farmers. The conclusion of this research is takhrij and syarah hadith about soil quality for farming with agrotechnology analysis.